2015
DOI: 10.17338/trainology.4.1_15
|View full text |Cite
|
Sign up to set email alerts
|

Validity of wireless device measuring velocity of resistance exercises

Abstract: Objectives:The purpose of the study was to identify the level of accuracy in velocity measurement from a newly developed inertia sensor. Design and Methods: Five subjects performed two dumbbell exercises for total of four sets of ten repetitions with a light intensity. Velocity data were taken and considered for analysis from two devices; the inertia sensor, wirelessly connected via Bluetooth™ to a smartphone, and a motion capture system. Both data were taken at the sampling frequency of 200 Hz. Identical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 10 publications
2
31
0
3
Order By: Relevance
“…Sato et al (35) also suggested that PUSH TM is highly valid at measuring movement velocity in the dumbbell biceps curl and dumbbell shoulder press. However, the Pearson correlation analyses employed in both studies (5,35) involved combining all repetitions performed by each individual. That is, all participants provided multiple data points in each paired measure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sato et al (35) also suggested that PUSH TM is highly valid at measuring movement velocity in the dumbbell biceps curl and dumbbell shoulder press. However, the Pearson correlation analyses employed in both studies (5,35) involved combining all repetitions performed by each individual. That is, all participants provided multiple data points in each paired measure.…”
Section: Introductionmentioning
confidence: 99%
“…Despite receiving considerable academic and practitioner interest in recent years, the test-retest reliability of the PUSH TM device is yet to be determined. Previous studies have either not employed a repeated measures design that permits a test-retest analysis (5,35) and/or have not reported any reliability statistics (6,35). Similarly, the smallest difference between repeated trials that is not due to measurement error or variation within individual performance, termed the smallest worthwhile change (SWC) (22), has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…The device has shown to be a valid tool for the measurement of concentric barbell velocity. 13 The device was attached to each participant's forearm. Prior to the initial testing, subject anthropometric measurements were collected.…”
Section: Methodsmentioning
confidence: 99%
“…It has been established that a load-velocity relationship (r = ~0.95) exists during progressive resistance training tests. 7,11 However, VBT is typically only investigated for dumbbell 13 or barbell 11,14 exercises. Other common resistance training exercises, such as medicine ball variations, should also be explored if practitioners are interested in quantifying and prescribing resistance training loads.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these devices have been tested for validity and reliability in dumbbell and barbell exercises using gold standard criterions. 2,13 However, medicine ball exercises present a unique challenge for technology manufacturers because of the versatile nature of many medicine ball exercise variations.…”
Section: Introductionmentioning
confidence: 99%